Composite particle and preparation method thereof

By mixing positively charged micro-scale metal particles and nano-scale oxide particles in water in a 3D printer, and using ultra-fine bubbles to adhere, the problem of uneven coating of nano-scale particles in the prior art is solved, and the problem of uneven coating of nano-scale particles is achieved Efficient composite particle manufacturing reduces the amount of agent used and improves the quality and performance of composite particles.

CN119136928APending Publication Date: 2024-12-13TOHOKU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202280095678.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-09
Filing Date
2022-09-05
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In 3D printers, it is difficult for the prior art to uniformly coat nano-scale oxide particles on the surface of micro-scale metal particles in water, resulting in the generation of impurity particles when laser or electron beams are irradiated, and a drug that uses polymer electrolytes to adjust the surface charges is adjusted using polymer electrolytes. The dose is large, affecting efficiency.

Method used

By mixing positively charged micrometer-level first particles and positively charged nanometer-level second particles in water, the second particles adhere to the surface of the first particles in the presence of ultra-fine bubbles to generate composite particles, avoiding the use of Polymer electrolyte and other agents.

Benefits of technology

With the absence of polymer electrolyte agents, nano-scale particles are uniformly attached to the surface of micro-scale particles, reducing the use of adhesion agents, improving the quality and performance of composite particles, and suitable for 3D printer modeling materials and other uses. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119136928A_ABST
    Figure CN119136928A_ABST
Patent Text Reader

Abstract

A method for producing composite particles, which comprises a step of mixing first particles positively charged in water and second particles positively charged in water, the average particle diameter of which is smaller than that of the first particles, in an aqueous medium in the presence of ultra-fine bubbles, and causing the second particles to adhere to the surfaces of the first particles to produce composite particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to composite particles and a method for producing the same.

[0002] This application claims priority based on PCT / JP2022 / 019729, an international application filed on May 9, 2022, and the contents of which are incorporated herein by reference. Background Art

[0003] Metal particles with a particle size of micrometers are used as modeling materials for 3D printers. 3D printers create models by irradiating metal particles with lasers or electron beams, melting them quickly, and solidifying them into the desired shape.

[0004] In 3D printers, in order to reduce the energy when melting metal particles, it is effective to modify the surface state of the metal particles and increase the absorption rate of laser or electron beam. As a method for modifying the surface state of metal particles, a method of enlarging the surface area by coating the surface of metal particles with inorganic particles having a particle size of nanometers is considered. As inorganic particles, oxide particles having a higher melting point than metal particles are considered. However, metal particles are positively charged in water, and oxide particles are also positively charged in water. Therefore, if metal particles and oxide particles are mixed in water, the two repel each other. Therefore, it is difficult to uniformly coat the surface of metal particles with oxide particles in water.

[0005] As a method for producing composite particles in which nano-scale particles are attached to the surface of micron-scale particles, there is known a method of adjusting the surface charge of a mother particle (micron-scale particle) and a daughter particle (nano-scale particle), mixing them in a liquid, and combining the two by electrostatic attraction to form a composite (Patent Document 1). In Patent Document 1, as a method for adjusting the surface charge of a mother particle and a daughter particle, a method of adsorbing a polymer electrolyte on a mother particle and a daughter particle is described.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: International Publication No. 2017 / 099250 Summary of the invention

[0009] Problem that the invention aims to solve

[0010] Particles used as modeling materials for 3D printers are preferably particles that do not generate impurities when irradiated with laser light, etc. Therefore, when producing composite particles, it is desirable to use a small amount of agents for adjusting surface charges, such as polymer electrolytes.

[0011] The present invention was completed in view of the above situation, and its purpose is to provide a method for producing composite particles that can make nano-scale microparticles adhere to the surface of micron-scale particles even without using agents for adjusting surface charge such as polymer electrolytes, and composite particles with a small amount of adhesion of agents for adjusting surface charge.

[0012] Technical Solution

[0013] The present inventors discovered that by mixing first particles that are positively charged in water and second particles that have an average particle size smaller than that of the first particles and are positively charged in water in an aqueous medium in the presence of ultrafine bubbles, the second particles can be attached to the surface of the first particles even without using agents such as polymer electrolytes for adjusting the surface charge, thereby completing the present invention.

[0014] Therefore, the present invention has the following aspects.

[0015] [1] A method for producing composite particles, comprising the steps of mixing first particles that are positively charged in water and second particles that are smaller in average particle size than the first particles and are positively charged in water in an aqueous medium in the presence of ultrafine bubbles, and allowing the second particles to adhere to the surface of the first particles to generate composite particles.

[0016] [2] The method for producing composite particles according to [1], wherein the average particle size of the second particles is within a range of 1 / 10000 to 1 / 10 of the average particle size of the first particles.

[0017] [3] The method for producing composite particles according to [1] or [2], wherein the average particle size of the first particles is in the range of 1 μm to 1000 μm.

[0018] [4] The method for producing composite particles according to any one of [1] to [3], wherein the average particle size of the second particles is within a range of 1 nm to 500 nm.

[0019] [5] A composite particle produced by the production method described in any one of [1] to [4], wherein the content of the second particle is in the range of 0.2 mass % to 20 mass % relative to the total mass of the composite particle, and the circularity of the first particle is in the range of 0.8 to 0.99.

[0020] [6] The composite particle according to [5], wherein the content of the second particles is in a range of 0.2 mass % to 10 mass % relative to the total mass of the composite particle.

[0021] [7] The composite particle according to [5] or [6], wherein the circularity of the first particle is in the range of 0.85 to 0.99.

[0022] [8] The composite particles according to [5], wherein the first particles are titanium-aluminum-vanadium alloy, and the second particles are aluminum oxide or zirconium oxide.

[0023] Effects of the Invention

[0024] According to the present invention, a method for producing composite particles that can attach nano-scale microparticles to the surface of micro-scale particles without using agents for adjusting surface charge such as polymer electrolytes, and composite particles with a small amount of agents for adjusting surface charge attached can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a conceptual diagram of a method for producing composite particles according to one embodiment of the present invention.

[0026] Figure 2 This is a SEM photograph of the dry powder obtained in Example 1.

[0027] Figure 3 This is a SEM photograph of the dry powder obtained in Example 2.

[0028] Figure 4 This is a SEM photograph of the dry powder obtained in Example 3.

[0029] Figure 5 This is a SEM photograph of the Ti6Al4V powder used in Examples 1 to 3.

[0030] Figure 6 This is a STEM image of an L-PBF molded body obtained using the composite particles obtained in Example 3.

[0031] Figure 7 These are a close-up HRTEM image and SAED pattern of the L-PBF molded body obtained using the composite particles obtained in Example 3.

[0032] Figure 8 This is the indentation depth-load curve of the L-PBF molded body obtained using the composite particles obtained in Example 3.

[0033] Fig. 9 This is the indentation depth-load curve of the L-PBF molded body obtained using the Ti6Al4V powder used in Examples 1 to 3.

[0034] Fig.10 (a) is a top view of a powder bed quality evaluation device for layered molding used in the adhesion evaluation test of Example 5, Fig.10 (b) is Fig.10 (a) bb line cross-sectional view.

[0035] Fig.11 (a) is a SEM photograph of the zirconia / Ti6Al4V composite particles before the bonding evaluation test performed in Example 5. Fig.11 (b) is an enlarged SEM photograph.

[0036] Fig.12 (a) is a SEM photograph of the zirconia / Ti6Al4V composite particles after the first bonding evaluation test performed in Example 5. Fig.12 (b) is an enlarged SEM photograph.

[0037] Fig.13 (a) is a SEM photograph of the zirconia / Ti6Al4V composite particles after the second adhesion evaluation test performed in Example 5. Fig.13 (b) is an enlarged SEM photograph.

[0038] Fig.14 (a) is a SEM photograph of the zirconia / Ti6Al4V composite particles after the third adhesion evaluation test performed in Example 5. Fig.14 (b) is an enlarged SEM photograph.

[0039] Fig.15 (a) is a SEM photograph of the zirconia / Ti6Al4V composite particles after the fourth bonding evaluation test performed in Example 5. Fig.15 (b) is an enlarged SEM photograph.

[0040] Fig.16 (a) is a SEM photograph of the zirconia / Ti6Al4V composite particles after the fifth bonding evaluation test performed in Example 5. Fig.16 (b) is an enlarged SEM photograph.

[0041] Fig.17 This is an engineering stress-strain curve obtained in a tensile test when the zirconia / Ti6Al4V composite particles obtained in Example 6 are used.

[0042] Fig.18 This is an engineering stress-strain curve obtained in a tensile test when Ti6Al4V single particles are used as a reference example. DETAILED DESCRIPTION

[0043] Hereinafter, the present embodiment will be described in detail with reference to the accompanying drawings as appropriate. The accompanying drawings used in the following description may sometimes enlarge the characteristic parts for convenience in order to facilitate understanding of the characteristics of the present invention, and sometimes the dimensional ratios of the various components are different from the actual ones. The materials, dimensions, etc. shown in the following description are examples, and the present invention is not limited thereto, and may be appropriately changed and implemented within the scope of not changing the main purpose thereof.

[0044] Figure 1 This is a conceptual diagram of a method for producing composite particles according to one embodiment of the present invention.

[0045] like Figure 1 As shown, in the method for producing composite particles of the present embodiment, first particles 1 and second particles 2 are mixed in an ultrafine bubble-containing dispersion 4 containing ultrafine bubbles 3. The ultrafine bubble-containing dispersion 4 can be prepared, for example, by the following method: a method of mixing a mixed aqueous dispersion in which the first particles 1 and the second particles 2 are dispersed with ultrafine bubble water containing ultrafine bubbles 3; a method of mixing a dispersion of the first particles 1 containing ultrafine bubbles 3 with a dispersion of the second particles 2 containing ultrafine bubbles 3.

[0046] The first particle 1 and the second particle 2 are particles that are positively charged in water. In contrast, the ultrafine bubbles 3 are negatively charged in water. The first particle 1 and the second particle 2 dispersed in the dispersion 4 containing ultrafine bubbles are electrically neutralized by the ultrafine bubbles 3. By electrically neutralizing the first particle 1 and the second particle 2, the two particles attract each other through intermolecular forces. As a result, a plurality of second particles 2 are attached to the surface of the first particle 1 to generate composite particles.

[0047] The average particle size of the first particles 1 is, for example, in the range of 0.1 μm or more and 1000 μm or less. The lower limit of the average particle size of the first particles 1 is preferably 5 μm or more, and more preferably 10 μm or more. In addition, the upper limit of the average particle size of the first particles 1 is preferably 500 μm or less, and more preferably 100 μm or less. The average particle size of the second particles 2 is, for example, in the range of 1 nm or more and 500 nm or less. The lower limit of the average particle size of the second particles 2 is preferably 5 nm or more, and more preferably 10 nm or more. In addition, the upper limit of the average particle size of the second particles 2 is preferably 300 nm or less, and more preferably 100 nm or less. The average particle size of the second particles 2 is, for example, in the range of 1 / 10000 or more and 1 / 10 or less, preferably in the range of 1 / 5000 or more and 1 / 50 or less, and more preferably in the range of 1 / 2000 or more and 1 / 500 or less relative to the average particle size of the first particles 1.

[0048] The average particle diameter of the first particles 1 and the second particles 2 may be, for example, an average value of particle diameters of 100 particles measured using a SEM (scanning electron microscope).

[0049] The materials of the first particle and the second particle are not particularly limited. The materials of the first particle 1 and the second particle may be the same or different. As the materials of the first particle and the second particle, for example, metals, metalloids, oxides, hydroxides, carbonates, carbides, nitrides, borides, etc. can be used. Examples of metals include Mg, Ca, Sr, Ba, Sc, Y, La, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zr, Nb, Mo, Ru, Ag, W, Al, Zn, Ga, In, Sn, Pb, Bi, and alloys of these metals. Examples of metalloids include Si, Ge, and Sb. Examples of oxides include magnesium oxide, calcium oxide, iron oxide, titanium oxide, zirconium oxide, zinc oxide, aluminum oxide, and silicon oxide. Examples of hydroxides include magnesium hydroxide, calcium hydroxide, and aluminum hydroxide. Examples of carbonates include lithium carbonate, magnesium carbonate, calcium carbonate, and barium carbonate. Examples of carbides include calcium carbide, silicon carbide, and titanium carbide. Examples of nitrides include silicon nitride and titanium nitride. Examples of borides include iron boride and titanium boride. Examples of preferred combinations of these materials include a combination in which one of the materials of the first particle 1 and the second particle 2 is an oxide (particularly magnesium oxide, aluminum oxide, zirconium oxide) and the other is a metal (particularly Ti, Fe, Ni, Zr, Al). As an example, a combination in which the first particle 1 is a titanium-aluminum-vanadium alloy and the second particle is an aluminum oxide or a zirconium oxide can be cited.

[0050] Ultrafine bubbles 3 are also called nanobubbles, and as specified in JIS B 8741-1:2019 (Microbubble Technology - General Rules for the Use and Measurement of Microbubbles Part 1: Terminology), they refer to microbubbles with an equivalent volume diameter of less than 1 μm. Ultrafine bubble water is a liquid in which diffuse reflection of laser light caused by ultrafine bubbles 3 can be confirmed when laser light is irradiated. It should be noted that the ultrafine bubble-containing dispersion 4 may also contain microbubbles (microbubbles).

[0051] Ultrafine bubble water is, for example, water in which ultrafine bubbles 3 are generated in pure water. Pure water is high-purity water that does not contain impurities or contains impurities in very small amounts. As pure water, for example, pure water having an electrical conductivity of 1 μS / cm or less can be used. The type of gas that forms the ultrafine bubbles 3 is not particularly limited, and for example, air, oxygen, nitrogen, ozone, and carbon dioxide can be used.

[0052] In the present embodiment, by mixing the first particles 1 and the second particles 2 in the ultrafine bubble-containing dispersion 4 containing ultrafine bubbles 3, the deformation of the first particles 1 can be suppressed and the second particles 2 can be attached to the surface of the first particles 1, compared with the case where the first particles 1 and the second particles 2 are simply mixed without using ultrafine bubbles.

[0053] The content of the first particle 1 of the dispersion 4 containing ultrafine bubbles is, for example, in the range of 0.2 volume % or more and 1.5 volume % or less. The lower limit of the content of the first particle 1 is preferably 0.3 volume % or more, and more preferably 0.5 volume % or more. In addition, the upper limit of the content of the first particle 1 is preferably 1.2 volume % or less, and more preferably 1.0 volume % or less. The content of the second particle 2 of the dispersion 4 containing ultrafine bubbles is, for example, in the range of 0.02 volume % or more and 0.3 volume % or less. The lower limit of the content of the second particle 2 is preferably 0.02 volume % or more, and more preferably 0.05 volume % or more. In addition, the upper limit of the content of the second particle 2 is preferably 0.20 volume % or less, and more preferably 0.15 volume % or less. The mass ratio of the content of the second particles 2 to the content of the first particles 1 (content of the second particles / content of the first particles) is, for example, in the range of 1 / 1000 to 1 / 10, preferably in the range of 1 / 500 to 1 / 50, and more preferably in the range of 1 / 400 to 1 / 100.

[0054] The pH of the ultrafine bubble-containing dispersion 4 is, for example, in the range of 6 to 8. The zeta potential of the ultrafine bubble-containing dispersion 4 is, for example, in the range of -65 mV to -10 mV, preferably in the range of -60 mV to -10 mV.

[0055] The composite particles generated in the ultrafine bubble-containing dispersion 4 can be recovered by solid-liquid separation methods such as decantation or filtration. The recovered composite particles are usually dried. As a drying method, for example, vacuum drying can be used.

[0056] The composite particles obtained by the method for producing composite particles of the present embodiment include first particles 1 and a plurality of second particles 2 attached to the surface of the first particles 1. The content of the second particles 2 is in the range of 0.2 mass % to 20 mass %, preferably in the range of 0.2 mass % to 10 mass %, more preferably in the range of 0.2 mass % to 5 mass %, and further preferably in the range of 0.3 mass % to 5 mass %, relative to the total mass of the composite particles.

[0057] The content of the second particles 2 can be calculated using, for example, the following formula.

[0058] Content of second particles (mass %) = [(oxygen content in composite powder (mass %) - oxygen content in first particles (mass %)) / (atomic weight of oxygen × 2)] × atomic weight of second particles

[0059] In the composite particles obtained by the method for manufacturing composite particles of the present embodiment, the amount of the second particles 2 attached to the first particles 1, as the mass ratio of the content of the second particles 2 relative to the content of the first particles 1 (the content of the second particles / the content of the first particles), can be, for example, in the range of greater than 1 / 1200 and less than 1 / 12, preferably in the range of greater than 1 / 1100 and less than 1 / 13, and more preferably in the range of greater than 1 / 1000 and less than 1 / 14.

[0060] In the composite particles obtained by the method for producing composite particles of the present embodiment, the circularity of the first particles 1 is in the range of 0.8 to 0.99, preferably in the range of 0.85 to 0.99, more preferably in the range of 0.85 to 0.95, and particularly preferably in the range of 0.9 to 0.95.

[0061] The circularity of the first particles 1 can be calculated, for example, by finding the average value of the circularity calculated from the area and the perimeter of the particles obtained by image analysis.

[0062] In addition, when the circularity of the first particle 1 before mixing is set to W1 and the circularity of the first particle 1 after mixing is set to W2, the absolute value of their difference (W1-W2) is preferably within the range of 0.1 or less, more preferably within the range of 0.05 or less, and further preferably within the range of 0.03 or less. If the first particle 1 and the second particle 2 are simply mixed without using ultrafine bubbles as in the previous method, when the second particle 2 is attached to the first particle 1, the surface of the first particle 1 is deformed to a certain extent and a depression is generated, and the second particle 2 enters the depression. Therefore, the circularity W2 of the first particle 1 after mixing is lower than the circularity W1 of the first particle 1 before mixing. On the other hand, if the first particle 1 and the second particle 2 are mixed using ultrafine bubbles as in the present embodiment, the surface of the first particle 1 is hardly deformed and the second particle is attached to the surface of the first particle 1 due to the intermolecular force between the first particle 1 and the second particle 2. Therefore, the reduction of the circularity W2 of the first particle 1 after mixing can be suppressed.

[0063] The composite particles can be made highly pure because the ultrafine bubble-containing dispersion 4 used in the production thereof does not particularly require components other than the first particles 1 , the second particles 2 , and the ultrafine bubbles 3 .

[0064] According to the method for producing composite particles of the present embodiment configured as above, since the first particles 1 and the second particles 2 are mixed in the presence of the ultrafine bubbles 3 , composite particles in which the second particles 2 are attached to the surface of the first particles 1 can be obtained.

[0065] In the method for producing composite particles of the present embodiment, when the average particle size of the second particles 2 is within a range of 1 / 5000 to 1 / 10 of the average particle size of the first particles 1 , the second particles 2 can be easily uniformly attached to the surface of the first particles 1 .

[0066] In addition, the composite particles obtained when the average particle size of the first particles 1 is within the range of 1 μm to 1000 μm and the average particle size of the second particles 2 is within the range of 1 nm to 500 nm can be used for various purposes such as modeling materials for laser 3D printers, catalysts, ceramic raw materials, etc.

[0067] Since the composite particles of this embodiment are manufactured using the manufacturing method of the composite particles of this embodiment, the second particles 2 are uniformly attached to the surface of the first particles and are of high purity. Therefore, the composite particles can be used for various purposes such as modeling materials for laser 3D printers, raw materials for powder metallurgy, optical devices, catalysts, ceramic raw materials, etc.

[0068] Composite particles used as a modeling material for a laser 3D printer, for example, use metal particles used as a modeling material for a laser 3D printer as the first particle 1, and use oxide particles with high laser absorption rate as the second particle 2. Compared with the first particle 1 alone, the composite particle forms a concave-convex shape by the second particle 2 attached to the surface of the first particle 1, so it is easier to melt and solidify due to laser irradiation than the first particle 1 alone. As the first particle 1, for example, Ti6Al4V, MoTiAl, NiAlCrMo, etc. can be used. In addition, as the second particle 2, for example, aluminum oxide and zirconium oxide can be used.

[0069] The composite particles used as the catalyst are, for example, inert and chemically stable particles as the first particles 1 and particles having a catalytic effect as the second particles 2. Since the second particles of the composite particles are attached to the surface of the first particles 1 without forming aggregated particles, the catalytic effect is higher than that of the second particles 2 alone.

[0070] The composite particles used as the ceramic raw material, for example, use particles containing a first element constituting the ceramic to be manufactured as the first particles 1, and use particles containing a second element constituting the ceramic to be manufactured as the second particles 2. Since the second particles 2 are uniformly attached to the surface of the first particles 1, the composition of the ceramic manufactured using the composite particles is uniform.

[0071] Example

[0072] [Example 1]

[0073] 5 parts by mass of alumina powder (purity: 99.9% by mass, average particle size: 125 nm) were added to 95 parts by mass of ion exchange water, stirred for 1 hour with a stirrer while cooling in an ice water bath, and then subjected to ultrasonic dispersion treatment to prepare an aqueous dispersion of alumina particles with a concentration of 5% by mass. Similarly, 5 parts by mass of Ti6Al4V powder (purity: 99.5% by mass, D10: 5.72 μm, D50: 14.06 μm, D90: 22.25 μm) were added to 95 parts by mass of ion exchange water, stirred for 1 hour with a stirrer while cooling in an ice water bath, and then subjected to ultrasonic dispersion treatment to prepare an aqueous dispersion of Ti6Al4V particles with a concentration of 5% by mass. Ti6Al4V powder used spherical particles manufactured by atomization.

[0074] The aqueous dispersion of aluminum oxide particles and the dispersion of Ti6Al4V particles were mixed in a mass ratio of 1:9, cooled in an ice-water bath, and stirred for 1 hour using a stirrer to obtain a mixed aqueous dispersion with a solid content concentration of 5% by mass. The content of aluminum oxide in the mixed aqueous dispersion was 0.63% by volume, and the content of Ti6Al4V was 0.56% by volume. While stirring the obtained mixed aqueous dispersion with a stirrer, ultrafine bubble water (manufactured by Japan Tungsten Co., Ltd., ZETA potential: -20mV) was added to the mixed aqueous dispersion using a separatory funnel. The ZETA potential of the mixed aqueous dispersion after the addition of ultrafine bubble water was -15mV. It should be noted that the ZETA potential of the ultrafine bubble water was measured using a nanoparticle sizer (SZ-100, manufactured by Horiba, Ltd.).

[0075] After the titration of the ultrafine bubble water was completed, the stirrer was stopped, the mixed aqueous dispersion was filtered, and the solid content was recovered. The recovered solid content was vacuum dried at a temperature of 298K to obtain a dry powder.

[0076] [Example 2]

[0077] A dry powder was obtained in the same manner as in Example 1 except that the concentration of the aqueous dispersion of alumina particles and the aqueous dispersion of Ti6Al4V particles was 10% by mass. The content of alumina in the mixed aqueous dispersion was 1.2% by volume, and the content of Ti6Al4V was 1.1% by volume.

[0078] [Example 3]

[0079] A dry powder was obtained in the same manner as in Example 1 except that zirconium oxide powder (purity: 99.9 mass %, average particle size: 53 nm) was used instead of alumina powder and the concentration of the aqueous dispersion of zirconium oxide particles and the aqueous dispersion of Ti6Al4V particles was 10 mass %. The content of zirconium oxide in the mixed aqueous dispersion was 0.38 volume %, and the content of Ti6Al4V was 1.1 volume %.

[0080] [evaluate]

[0081] (1) Surface shape of particles

[0082] The particle surfaces of the dry powders obtained in Examples 1 to 3 were observed using a scanning electron microscope. Figure 2 The SEM photograph of the dry powder obtained in Example 1 is shown. Figure 3 The SEM photograph of the dry powder obtained in Example 2 is shown. Figure 4 The SEM photograph of the dry powder obtained in Example 3 is shown. Figure 5 The SEM photographs of the Ti6Al4V powders used in Examples 1 to 3 are shown.

[0083] If you compare Figure 2 to Figure 4 and Figure 5 From the SEM photographs of , it was confirmed that in Examples 1 and 2, composite particles in which alumina particles were attached to the surface of Ti6Al4V particles were generated, and in Example 3, composite particles in which zirconia particles were attached to the surface of Ti6Al4V particles were generated.

[0084] (2) Laser Forming Processability

[0085] The zirconium oxide / Ti6Al4V composite particles obtained in Example 3 were melted and solidified by powder bed laser melting (L-PBF) to obtain an L-PBF molded body. As a laser light source, a Yb:YAG fiber laser light source (made by Raycus Fiber Laser Technology, Wuhan, laser wavelength: 1070nm, maximum output power: 22W) was used. The laser irradiation was carried out in a high-purity argon atmosphere at a laser output power of 20.6W and a scanning speed of 10mm·s -1 , scanning interval: 100μm, layer thickness: 25μm. In addition, the molten zirconia / Ti6Al4V composite particles were condensed at a rate of 10 3 ~10 8 The L-PBF molded body is a cuboid with a width of 4 mm, a length of 4 mm, and a height of 1.4 mm.

[0086] The STEM image of the obtained L-PBF structure is shown in Figure 6, the close-up HRTEM image and SAED pattern are shown in Figure 7 .Depend on Figure 6 and Figure 7 The results show that due to 10 3 ~10 8 The high solidification rate of K / s makes the obtained L-PBF molded body consist of fine martensite. Figure 7 No ceramic phase was detected in the close-up HRTEM image shown. This is believed to indicate that the zirconia was decomposed and dissolved in α'-Ti by the irradiation of the high-energy laser. Figure 6 From the element distribution in L-PBF, it can be seen that zirconium is evenly distributed in the structure without significant segregation due to the thermodynamic imbalance characteristics of L-PBF.

[0087] The mechanical strength of the L-PBF molded body was measured by a press-in test. Figure 8 This is the indentation depth-load curve of the L-PBF molded body obtained using zirconia / Ti6Al4V composite particles. Fig. 9 This is the penetration depth-load curve of the L-PBF molded body obtained using Ti6Al4V particles.

[0088] Depend on Figure 8 and Fig. 9 The results show that the L-PBF molded body obtained using zirconia / Ti6Al4V composite particles has a shallower indentation depth and higher rigidity when the same load is applied than the L-PBF molded body obtained using Ti6Al4V particles.

[0089] In addition, the Vickers hardness of the L-PBF molded body obtained using the zirconium oxide / Ti6Al4V composite particles and the L-PBF molded body obtained using the Ti6Al4V particles was measured by a micro Vickers hardness tester (HM-200, manufactured by Mitutoyo Co., Ltd.). As a result, the Vickers hardness of the L-PBF molded body obtained using the zirconium oxide / Ti6Al4V composite particles was 714 HV, which was significantly higher than the Vickers hardness (519 HV) of the L-PBF molded body obtained using the Ti6Al4V composite particles.

[0090] The above results confirm that the zirconium oxide / Ti6Al4V composite particles obtained in Example 3 are effective as a modeling material for a laser 3D printer.

[0091] [Example 4]

[0092] Ultrafine bubble water and pure water were mixed in the amounts shown in Table 1 below to prepare 500 mL of aqueous media No. 1 to 5. Ultrafine bubble water used was ultrafine bubble water having a zeta potential of -47.1 mV prepared using pure water as a raw material and a bubble production time of 10 hours. In addition, Ti6Al4V powder and zirconium oxide powder used in Example 3.

[0093] Into 500mL of aqueous medium No.1 to 5, add 9g of Ti6Al4V powder and 1g of zirconium oxide powder respectively. Then, use a stirrer to mix for 20 minutes to prepare a mixed aqueous dispersion. After the stirring is completed, filter the mixed aqueous dispersion and recover the solid content. The recovered solid content is vacuum dried at a temperature of 298K to obtain a composite powder. The oxygen content (mass %) of the obtained composite powder is measured using an oxygen-nitrogen-hydrogen analyzer (ONH836, manufactured by LECO). The zirconium oxide powder content in the composite powder is calculated using the following formula based on the obtained oxygen content and the previously measured oxygen content of the Ti6Al4V powder (0.2334 mass %).

[0094] Zirconia powder content (mass %) = [(oxygen content in composite powder (mass %) - oxygen content in Ti6Al4V powder (mass %)) / (atomic weight of oxygen × 2)] × atomic weight of ZrO2

[0095] The oxygen content, oxygen increase, and zirconium oxide powder content of the composite powder are shown in Table 1. The oxygen increase is the oxygen content obtained by subtracting the oxygen content of the Ti6Al4V powder from the oxygen content of the composite powder.

[0096] [Table 1]

[0097]

[0098] From the results in Table 1, it can be seen that the zirconium oxide powder content of the composite powder increases as the amount of ultrafine bubble water in the aqueous medium increases. This is because as the amount of ultrafine bubble water increases, the amount of nano-scale zirconium oxide attached to the surface of the micron-scale Ti6Al4V powder increases, and when the mixed aqueous dispersion after stirring is filtered, the amount of zirconium oxide lost to the outside decreases.

[0099] [Example 5]

[0100] 100 g of zirconia / Ti6Al4V composite particles were prepared in the same manner as in Example 3 except that the zirconia particle aqueous dispersion and the Ti6Al4V particle aqueous dispersion were mixed at a mass ratio of 5:95. The bonding evaluation test of the zirconia particles and the Ti6Al4V composite particles of the obtained zirconia / Ti6Al4V composite particles was conducted using a powder bed quality evaluation apparatus for layered molding (PBQ-3, manufactured by Toei Science Industry Co., Ltd.).

[0101] Fig.10 (a) is a top view of a powder bed quality evaluation device for layered molding used in a bonding evaluation test. Fig.10 (b) is Fig.10 The powder bed quality evaluation device 10 for layered molding includes a device body 11 , a particle supply platform 12 , a molding platform 13 , an overflow particle recovery cup 14 , and a scraper 15 .

[0102] The particle supply platform 12 and the modeling platform 13 are disposed adjacent to each other on the surface of the apparatus body 11. The overflow particle recovery cup 14 is disposed on the modeling platform 13 at a position on the opposite side to the particle supply platform 12.

[0103] The particle supply platform 12 and the molding platform 13 each have a quadrilateral shape when viewed from above. The particle supply platform 12 and the molding platform 13 can move in the up and down directions respectively. The molding platform 13 is a nickel-plated steel flat plate (surface roughness Ra: 3.87 μm). The scraper 15 can move along the surface of the device body 11 from the particle supply platform 12 to the overflow particle recovery cup 14. The scraper 15 is a scraper for a laser lamination molding device (manufactured by Concept Laser, Y-shape lip 120 mm).

[0104] The particle binding evaluation test was performed as follows.

[0105] (1) The particle supply platform 12 is moved downward to form a step 12 a between the particle supply platform 12 and the device main body 11 .

[0106] (2) The step 12a of the particle supply platform 12 is filled with the sample 20 (zirconia / Ti6Al4V composite powder) to make the surface flat.

[0107] (3) The particle supply stage 12 is moved upward by 60 μm, so that the sample 20 protrudes from the apparatus main body 11 at a height of 60 μm. Furthermore, the modeling stage 13 is moved downward by 25 μm, so that a step 13 a is formed between the modeling stage 13 and the apparatus main body 11 .

[0108] (4) The scraper 15 is moved at a speed of 75 mm / s from the end of the particle supply platform 12 on the side opposite to the molding platform 13 toward the overflow particle recovery cup 14. In this way, the sample 20 protruding from the device body 11 is cut, and the cut sample 20 is moved to the molding platform 13, a part of the sample 20 is laid on the step 13a of the molding platform 13 (re-coating), and the remaining sample 20 is moved to the overflow particle recovery cup 14. The overflow particle recovery cup 14 recovers the remaining sample 20 that is not laid on the step 13a of the molding platform 13.

[0109] (5) The scraper 15 is returned to the end portion of the particle supply platform 12 on the side opposite to the molding platform 13 side.

[0110] (6) The above operations (3) to (5) are performed until the sample 20 filled in the step 12 a of the particle supply stage 12 disappears.

[0111] (7) 1 g of the sample 20 laid on the step 13 a of the molding platform 13 is selected, and the selected sample 20 is observed using a SEM.

[0112] The binding property evaluation test was repeated five times. In the second and subsequent evaluation tests, the sample 20 recovered from the overflow particle recovery cup 14 in the previous evaluation test was used.

[0113] Fig.11 (a) is a SEM photograph of the zirconia / Ti6Al4V composite particles before the bonding evaluation test. Fig.11 (b) is an enlarged SEM photograph. Figure 12 to Figure 16 (a) is a SEM photograph of the zirconia / Ti6Al4V composite particles after the bonding evaluation test. Figure 12 to Figure 16 (b) is an enlarged SEM photograph. Fig.12 It's the first time, Fig.13 The second time, Fig.14 The third time, Fig.15 It's the fourth time. Fig.16 This is a SEM photograph after the fifth bonding evaluation test.

[0114] If you compare Fig.11 SEM photos and Figure 12 to Figure 16 According to the SEM photographs, no significant changes were found in the surface state of the zirconium oxide / Ti6Al4V composite particles before and after the bonding evaluation test. This result confirms that the zirconium oxide / Ti6Al4V composite particles manufactured by the method of the present invention have high bonding between the zirconium oxide particles and the Ti6Al4V particles, and the zirconium oxide particles are not easy to fall off by re-coating with the scraper 15 (scraper for laser lamination molding device).

[0115] [Example 6]

[0116] 100 g of zirconium oxide / Ti6Al4V composite particles were produced in the same manner as in Example 3 except that the concentration of the zirconium oxide particle aqueous dispersion and the Ti6Al4V particle aqueous dispersion was 1 mass %.

[0117] [Example 7]

[0118] 100 g of zirconia / Ti6Al4V composite particles were produced in the same manner as in Example 3 except that the concentration of the zirconia particle aqueous dispersion and the Ti6Al4V particle aqueous dispersion was 5 mass %.

[0119] (Determination of circularity)

[0120] The circularity of the Ti6Al4V particles in the obtained zirconium oxide / Ti6Al4V composite particles was measured. The circularity was measured using an optical microscope (BX51, manufactured by OLYMPUS Co., Ltd.) and analysis software (WinROOF V6.5, manufactured by Mitani Sangyo Co., Ltd.). The circularity C of each particle was calculated by the following formula according to the international standard ISO 9276-6.

[0121] C=4πA / P 2

[0122] Where A is the area of ​​the particle (number of pixels) and P is the perimeter.

[0123] The circularity described above is an average value of circularities C calculated from 200 particles selected at random.

[0124] In addition, the circularity of the Ti6Al4V particles in the alumina / Ti6Al4V composite particles obtained in Example 1, the circularity of the Ti6Al4V particles in the zirconia / Ti6Al4V composite particles obtained in Example 3, and the circularity of the Ti6Al4V single particles as a reference example were calculated in the same manner as in Examples 6 to 7. The results are shown in Table 2.

[0125] [Table 2]

[0126]

[0127] From the results in Table 2, it is confirmed that in Example 1, the circularity of the alumina / Ti6Al4V composite particles is in the range of 0.88 to 0.96, which is slightly different from the circularity of the Ti6Al4V single particle (0.89 to 0.97), and the decrease in circularity can be suppressed. Similarly, it is confirmed that in Examples 3, 6, and 7, the circularity of the zirconium oxide / Ti6Al4V composite particles is in the range of 0.86 to 0.98, which is slightly different from the circularity of the Ti6Al4V single particle, and the decrease in circularity can be suppressed.

[0128] (Determination of mechanical strength)

[0129] The zirconium oxide / Ti6Al4V composite particles obtained in Example 6 were used to make a molded body by laser three-dimensional powder bed melting (L-PBF). The molding was performed using a layer molding device (MlabR, manufactured by ConceptLaser) equipped with a 1070nm ytterbium (Yb) fiber laser. The molding conditions were: laser output power 95W, scanning speed 800mm·s -1 , scanning width 90μm, powder thickness 25μm. The L-PBF molded body is a rectangular parallelepiped with a width of 6mm, a length of 30mm, and a height of 6mm. The L-PBF process is carried out in an argon (Ar) gas atmosphere, and the oxygen concentration is maintained below 0.1% by mass.

[0130] The mechanical strength of the obtained L-PBF molded body was measured by tensile test. A dumbbell-shaped test piece was cut from the L-PBF molded body, and the stress-strain curve was obtained using the test piece. In addition, as a comparison, the L-PBF molded body was obtained by melting and solidifying Ti6Al4V monomer particles by powder bed laser melting (L-PBF), and the engineering stress-strain curve was obtained using the test piece cut by the same molding method as above. These results are shown in Fig.17 and Fig.18 .

[0131] Depend on Fig.17 The results show that when using zirconia / Ti6Al4V composite particles, the tensile strength is 1210MPa (±16MPa), the yield strength is 1397MPa (±3MPa), and the elongation is 8.1% (±0.7%). Fig.18 The results show that when using Ti6Al4V particles alone, the tensile strength is 1167MPa (±2MPa), the yield point is 1312MPa (±9MPa), and the elongation is 6.4% (±0.8%). This confirms that the tensile strength, yield strength, and elongation of the molded body using zirconium oxide / Ti6Al4V composite particles are all improved compared to the molded body using Ti6Al4V single particles.

[0132] Description of Reference Numerals

[0133] 1: first particle;

[0134] 2: Second particle;

[0135] 3: Ultra-fine bubbles;

[0136] 4: Dispersion containing ultrafine bubbles;

[0137] 10: Powder bed quality evaluation device for stacking modeling;

[0138] 11: Device body;

[0139] 12: Particle supply platform;

[0140] 12a: stairs;

[0141] 13: Modeling platform;

[0142] 13a: stairs;

[0143] 14: Overflow particle recovery cup;

[0144] 15: scraper;

[0145] 20: Sample.

Claims

1. A method for producing composite particles, comprising the steps of: mixing first particles that are positively charged in water and second particles that are smaller in average particle size than the first particles and are positively charged in water in an aqueous medium in the presence of ultrafine bubbles, and allowing the second particles to adhere to the surface of the first particles to generate composite particles.

2. The method for producing composite particles according to claim 1, wherein: The average particle size of the second particles is within a range of 1 / 10000 to 1 / 10 of the average particle size of the first particles.

3. The method for producing composite particles according to claim 1 or 2, wherein: The average particle size of the first particles is within a range of 1 μm to 1000 μm.

4. The method for producing composite particles according to claim 1 or 2, wherein: The average particle size of the second particles is within a range of 1 nm to 500 nm.

5. A composite particle produced by the method according to claim 1, wherein: The content of the second particles is in the range of 0.2 mass % or more and 20 mass % or less relative to the total mass of the composite particles. The circularity of the first particles is within a range of 0.8 to 0.

99.

6. The composite particle according to claim 5, wherein The content of the second particles is in the range of 0.2 mass % or more and 10 mass % or less relative to the total mass of the composite particles.

7. The composite particle according to claim 5 or 6, wherein The circularity of the first particles is within a range of 0.85 to 0.

99.

8. The composite particle according to claim 5, wherein The first particle is a titanium-aluminum-vanadium alloy, The second particles are aluminum oxide or zirconium oxide.